Efektivitas Layanan Bimbingan Kelompok dengan Media Cynema Theraphy Untuk Meningkatkan Self Efficacy Siswa - Aginza, Iga Vinaya; Lathifah, Maghfirotul (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This study aims to determine the effectiveness of using the cynema therapy media in group guidance to increase student self-efficacy. This research approach is quantitative. This type of research uses the One Group Pre-Test Post-Test Design research design. This study consisted of the dependent variable, namely self-efficacy and the independent variable, namely group guidance services using cynema therapy media. The population in this study were high school and vocational high school students in RT 3 and 4 in Kepuh Kiriman village, from that population, 5 students were taken using a purposive sampling technique. The results of this study indicate that there is an increase in the average score of students' self-efficacy in Kepuh Kiriman village from the pre-test average score of 36.2 in the low category and the average score after the student was given treatment, the average post-test result was 66 high category. Thus, it proves that there is a significant influence on the use of cynema therapy media in group guidance to increase student self-efficacy.